(untitled) (Fiep Bulletin - online, 2013)
This article depicts preliminar analysis upon the based and control variables that are fundamental pre-requisites for a comprehensive diagonsis of the Brazilian sports system. In order to successful collect valid and reliable data it seems necessary to develop rigorous procedures of observation and effective instruments of investigation towards a continuous monitoring process, which is based on the European model (COMPASS). The central elements focus of this analysis deal with the notion of the object (sports participation) and the development of instruments that will elicit an indepth understanding of its reality, concepts, contexts in dynamic reality and not as a static or unidimensional phenomena. Variables are conclusively suggested as well as models for standardized data collection about sports systems, its implications, contraints, contradictions, controversies and overcomings. In sum, the authors suggest the analyses of subject that participate or not of sports and that adhere or not in physical activity as a blue print of universality in movement culture and adoption of sports as a fundamental human right.